Abrasion Wear Analysis of Commercial Cutting Inserts by Ball-on-disc Method - Dembiczak, Tomasz; Kruzel, Robert; Náprstková, Nataša; Bałaga, Zbigniew; Kuśmierczak, Sylvia; Wachowicz, Joanna; Reszka, Piotr (Manufacturing Technology Journal, 2024)
Today's machining requirements cannot be met without the right tool materials. An ideal universal tool material should combine the highest abrasive wear resistance and hardness with high strength and good toughness, while being chemically inert to the workpiece material. Despite the intensive development of materials sciences the fundamental contradiction between hardness, which guaran-tees resistance to abrasive wear, and toughness, which determines impact and fatigue strength, has not been satisfactorily resolved on a global scale. This paper presents the results of tribological wear testing of commercial cutting inserts of S20S, U10S and CC6090 grades. Chemical composition, den-sity, hardness and tribological wear were determined using the ball on disk method. The analysis of the laboratory tests showed that the S20S, U10S and CC6090 cutting inserts have high resistance to abrasive wear, the loss of total volumetric mass did not exceed 1%.
Keywords: Carbides; Tool ceramics; Tribological testing; Machining